Waterproof anticorrosive paint and preparation process thereof

By adding silicone particles to waterproof and anti-corrosion coatings and using them in conjunction with self-cleaning composite materials, combining the water absorption and water-releasing characteristics of silicone-tungstic acid and the photocatalytic properties of silicone-tungstic acid, the problem of insufficient self-cleaning and pollutant degradation capabilities of the coating is solved, achieving efficient self-cleaning and rapid degradation effects, and environmentally friendly and energy-saving.

CN119570312AActive Publication Date: 2025-03-07WORLDPECKER PAINT GRP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411776712.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-07
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The self-cleaning and improvement of existing waterproof and anti-corrosion coatings have limited capacity to degrade pollutants.

Method used

By adding silica gel particles to the coating and using them in conjunction with self-cleaning composite materials, the water absorption and water-releasing properties of silica gel particles are combined with the photocatalytic properties of silicotungstic acid, which significantly improves the self-cleaning ability of the coating and the degradation efficiency of organic pollutants.

Benefits of technology

It realizes efficient self-cleaning of the coating and rapid degradation of organic pollutants. It uses photocatalytic technology to save energy and be environmentally friendly without additional energy input, while maintaining excellent waterproof and corrosion resistance and construction performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a waterproof anticorrosive coating and a preparation process thereof, and relates to the technical field of coatings, and the waterproof anticorrosive coating comprises the following raw materials in parts by mass: 90-100 parts of a component A and 5-8 parts of a component B, the component A is prepared from the following raw materials in parts by mass: 55 to 60 parts of water-based fluorocarbon resin, 10 to 20 parts of water-based hydroxy acrylic resin, 1 to 2 parts of a self-cleaning composite material, 0.5 to 2.5 parts of silica gel particles, 0.2 to 1 part of a dispersing agent, 0.1 to 0.5 part of a defoaming agent, 0.5 to 1 part of a thickening agent, 1 to 2 parts of a film-forming agent and 10 to 20 parts of water; the component B is a curing agent; the silica gel particles are added and matched with the self-cleaning composite material for use, so that the water absorption and release characteristics of the silica gel particles are combined with the photocatalytic performance of silicotungstic acid, and the self-cleaning capacity of the coating and the degradation efficiency of the coating on organic pollutants are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of coatings, and in particular to a waterproof and anti-corrosion coating and a preparation process thereof. Background Art

[0002] Waterproof and anti-corrosion coating is a kind of coating that can prevent water penetration and corrosion damage to the substrate. It has excellent waterproof performance and corrosion resistance, which can effectively protect the substrate from erosion by moisture and corrosive substances, thereby extending the service life of the coating.

[0003] For example, the Chinese patent for waterproof and anti-corrosion coating for concrete and its preparation method with application number CN202210915407.1, this invention relates to the field of architectural coatings, specifically a waterproof and anti-corrosion coating for concrete and its preparation method. This invention prepares a waterproof and anti-corrosion coating for concrete, which uses water-based fluorocarbon resin as the base material, uses water-based hydroxy acrylic resin to improve its hydrophilicity, and uses the self-cleaning composite material made by this invention to improve its ability to remove dust and pollutants. Thus, a new type of coating that has the advantages of waterproof and anti-corrosion, high weather resistance, and chemical resistance of fluorocarbon coatings, and is dust-free and self-cleaning, is obtained. This invention uses nano-silica as the base material, and loads a layer of silicotungstic acid on the surface of nano-silica, uses trimethylsilyl imidazole as the modifier, and uses disodium EDTA and sodium dodecylbenzene sulfonate as surfactants, to obtain a self-cleaning composite material with good dispersibility and excellent photocatalytic performance.

[0004] Although the above scheme improves the coating's self-cleaning ability and ability to degrade pollutants to a certain extent, the improvement in the coating's self-cleaning and ability to degrade pollutants is limited. Summary of the invention

[0005] The embodiments of the present application provide a waterproof and anti-corrosion coating and a preparation process thereof, thereby further improving the coating's self-cleaning and pollutant degradation capabilities. By adding silica gel particles and using them in combination with a self-cleaning composite material, the water absorption and release properties of the silica gel particles are combined with the photocatalytic properties of silicotungstic acid, thereby significantly improving the coating's self-cleaning capability and organic pollutant degradation efficiency. Photocatalytic technology is used to degrade pollutants without the need for additional energy input, thereby saving energy and protecting the environment.

[0006] The embodiment of the present application provides a waterproof and anticorrosive coating, which includes the following raw materials, calculated by weight: 90-100 parts of component A, 5-8 parts of component B; The component A comprises the following raw materials, by mass: 55-60 parts of water-based fluorocarbon resin, 10-20 parts of water-based hydroxy acrylic resin, 1-2 parts of self-cleaning composite material, 0.5-2.5 parts of silica gel particles, 0.2-1 parts of dispersant, 0.1-0.5 parts of defoamer, 0.5-1 parts of thickener, 1-2 parts of film-forming agent, and 10-20 parts of water; The B component is a curing agent.

[0007] The preparation process of the waterproof and anticorrosive coating specifically comprises the following steps: (1) adding water, self-cleaning composite material, silica gel particles, and dispersant into a stirring tank, stirring at a low speed until uniform, and then adding water-based hydroxy acrylic resin, stirring at a high speed to obtain a stable slurry; (2) mixing the aqueous fluorocarbon resin with the stable slurry obtained in step (1) and stirring, adding a defoamer, a thickener, and a film-forming agent after stirring evenly, and stirring at high speed to obtain component A; (3) Component A obtained in step (2) is mixed with component B, and stirred at high speed to obtain the waterproof and anti-corrosion coating.

[0008] Furthermore, the method for preparing the self-cleaning composite material comprises the following steps: S1: tetraethyl orthosilicate and anhydrous ethanol are mixed and stirred to obtain solution A; then, anhydrous ethanol, water and hydrochloric acid are mixed and stirred to obtain solution B; then, solution B is added to solution A and stirred to obtain silica sol; S2: dissolving silicotungstic acid, surfactant and trimethylsilyl imidazole in water to obtain a silicotungstic acid solution, then adding the silica sol obtained in step S1 to the silicotungstic acid solution to obtain a suspension, filtering to obtain a filter cake, washing, drying and calcining to obtain the self-cleaning composite material; The surfactant is at least one of disodium EDTA and sodium dodecylbenzene sulfonate.

[0009] Furthermore, before adding the silica gel particles in step (1), they are pre-mixed and stirred with ethanol to form a uniform suspension.

[0010] Furthermore, the particle size of the silica gel particles is 10 nm-10 μm.

[0011] Furthermore, the component A also contains rubber powder. Specifically, the rubber powder is added to the stirring tank in step (1).

[0012] Furthermore, the rubber powder is 1-3 parts by mass.

[0013] Furthermore, the particle size of the rubber powder is 1-10 μm.

[0014] Furthermore, the rubber powder is also loaded with nano silicon dioxide.

[0015] Furthermore, the nano silicon dioxide accounts for 5%-15% of the mass of the rubber powder.

[0016] One or more technical solutions provided in the embodiments of the present application have at least the following technical effects or advantages: First, the pore structure of silica gel gives it a very high specific surface area, which enables it to absorb and store moisture. When silica gel is in a humid environment, the surface in its pores can absorb water vapor molecules in the air. When the humidity on the coating surface decreases or the temperature rises due to solar radiation, the silica gel particles will slowly release the stored moisture. The moisture adsorbed in the silica gel pores will gradually desorb and release into the surrounding environment, thereby promoting the photocatalytic reaction. Silica gel particles have strong hygroscopicity and can quickly absorb and release moisture. Adding silica gel particles to the coating can form tiny water absorption points on the coating surface, which can maintain the wetness of the coating surface, thereby promoting the photocatalytic reaction. The process accelerates the degradation of pollutants; silica gel has excellent weather resistance and chemical stability, and is not easy to react with other components in the coating. Silica gel particles can resist the erosion of ultraviolet rays and other environmental factors, extending the service life of the coating; by adding silica gel particles and using them in conjunction with self-cleaning composite materials, silica gel can continuously supply water to silicotungstic acid. The water absorption and release characteristics of silica gel particles combined with the photocatalytic properties of silicotungstic acid significantly improve the self-cleaning ability of the coating and the degradation efficiency of organic pollutants. The use of photocatalytic technology to degrade pollutants does not require additional energy input, which is energy-saving and environmentally friendly. At the same time, it ensures that the coating has excellent waterproof and anti-corrosion properties and construction performance; Secondly, the silica gel particles are pre-mixed with ethanol, and the wettability and dispersibility of ethanol are utilized to better disperse the silica gel particles in the coating; ethanol, as an organic solvent, can reduce the surface tension between silica gel particles, reduce agglomeration, and make the silica gel particles more evenly distributed in the coating; after the pre-formed silica gel suspension is added to the coating, the presence of ethanol can slow down the sedimentation rate of the silica gel particles, improve the stability of the coating system, and maintain the stability of the coating performance during storage and construction; ethanol, as a volatile solvent, will evaporate rapidly during the drying process of the coating, promote the film-forming process of the coating, and at the same time, the volatilization of ethanol will also drive the uniform distribution of silica gel particles on the coating surface, further improving the performance of the coating; silica gel particles of moderate particle size can form a uniform microporous structure in the coating, these microporous structures can improve the air permeability and wettability of the coating, and at the same time, the water absorption and release characteristics of the silica gel particles can also be better utilized, thereby further improving the self-cleaning ability of the coating and the degradation efficiency of organic pollutants; Third, rubber powder has a certain elasticity and absorption capacity, which can absorb part of the volume change when the paint absorbs water and expands, reduce the direct pressure on the paint structure, thereby maintaining the stability and durability of the paint, and improving the toughness of the paint, so that the paint has better crack resistance and durability when subjected to external stress or internal expansion pressure, prolonging the service life of the paint, and reducing the damage to the coating caused by stress concentration; rubber powder can change the stress distribution state inside the paint, disperse the concentrated compressive stress to a wider area, reduce the cracking or peeling of the coating caused by excessive local stress, thereby improving the overall performance of the coating; the addition of rubber powder further promotes the wettability and air permeability of the coating surface, and improves the self-cleaning ability of the coating. Since rubber powder forms a tiny pore structure in the coating, these pore structures promote the diffusion and discharge of water and pollutants; rubber powder and silica gel particles and self-cleaning composite materials produce synergistic effects in the coating. The elasticity and absorption capacity of rubber powder can maintain the stability and dispersibility of silica gel particles and self-cleaning composite materials in the coating, thereby further improving the performance of the coating; Fourthly, the rubber powder itself has good elasticity and toughness. After loading nano-silica, this composite material can more effectively absorb and disperse external impact or internal expansion pressure, thereby significantly improving the durability and crack resistance of the coating; nano-silica is easy to agglomerate due to its high specific surface area and surface activity, while loading it on rubber powder can effectively utilize the large specific surface area and pore structure of rubber powder to achieve uniform dispersion of nano-silica particles, prevent agglomeration, and improve the overall uniformity and stability of the coating; nano-silica has many excellent properties such as photocatalysis, UV resistance, and enhanced hardness. After loading it on rubber powder, these properties can be effectively retained and exerted in the coating. At the same time, the addition of rubber powder also makes the coating have better waterproofness and wear resistance; nano-silica, as a photocatalyst, requires the participation of water in the process of photocatalytic degradation of organic pollutants. Nano-silica loaded on rubber powder can be more evenly distributed in the coating, synergistically with silica gel particles, and continuously provide the required water for the photocatalytic reaction, thereby significantly improving the self-cleaning ability of the coating and the degradation efficiency of organic pollutants. DETAILED DESCRIPTION

[0017] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the term "and / or" used herein includes any and all combinations of one or more related listed items.

[0018] Embodiment 1: A waterproof and anticorrosive coating, comprising the following raw materials, by mass: 90-100 parts of component A, 5-8 parts of component B; The component A comprises the following raw materials, by mass: 55-60 parts of water-based fluorocarbon resin, 10-20 parts of water-based hydroxy acrylic resin, 1-2 parts of self-cleaning composite material, 0.5-2.5 parts of silica gel particles, 0.2-1 parts of dispersant, 0.1-0.5 parts of defoamer, 0.5-1 parts of thickener, 1-2 parts of film-forming agent, and 10-20 parts of water; The B component is a curing agent; The preparation process of the waterproof and anticorrosive coating comprises the following steps: (1) adding water, self-cleaning composite material, silica gel particles, and dispersant into a stirring tank, stirring at a low speed until uniform, and then adding water-based hydroxy acrylic resin, stirring at a high speed to obtain a stable slurry; (2) mixing the aqueous fluorocarbon resin with the stable slurry obtained in step (1) and stirring, adding a defoamer, a thickener, and a film-forming agent after stirring evenly, and stirring at high speed to obtain component A; (3) mixing component A and component B obtained in step (2), stirring at high speed, to obtain the waterproof and anticorrosive coating; The method for preparing the self-cleaning composite material comprises the following steps: S1: tetraethyl orthosilicate and anhydrous ethanol are mixed and stirred to obtain solution A; then, anhydrous ethanol, water and hydrochloric acid are mixed and stirred to obtain solution B; then, solution B is added to solution A and stirred to obtain silica sol; S2: dissolving silicotungstic acid, surfactant and trimethylsilyl imidazole in water to obtain a silicotungstic acid solution, then adding the silica sol obtained in step S1 to the silicotungstic acid solution to obtain a suspension, filtering to obtain a filter cake, washing, drying and calcining to obtain the self-cleaning composite material; The surfactant is at least one of disodium EDTA and sodium dodecylbenzene sulfonate; For the above embodiment, the specific implementation is as follows: The waterproof and anticorrosive coating comprises the following raw materials, calculated by mass: 95 parts of component A and 6 parts of component B; Among them, component A, by mass, includes the following raw materials: 59 parts of water-based fluorocarbon resin, 15 parts of water-based hydroxy acrylic resin, 1.5 parts of self-cleaning composite material, 1 part of silica gel particles, 0.5 parts of dispersant, 0.3 parts of defoaming agent, 0.7 parts of thickener, 2 parts of film-forming agent, and 15 parts of water; Component B is a curing agent; the curing agent is polyurethane; The dispersant was dispersant LBD-1; The defoamer is BNK-G303 defoamer; The thickener is water-based paint thickener C-100; The film former is alcohol ester dodecahydrate; The method for preparing a self-cleaning composite material comprises the following steps: S1: Mix 21 parts of tetraethyl orthosilicate and 19 parts of anhydrous ethanol by mass, and then stir at a speed of 280 r / min for 30 minutes to obtain solution A; then take 19 parts of anhydrous ethanol, 10 parts of water and 0.5 parts of hydrochloric acid and mix them, and then stir at a speed of 280 r / min for 30 minutes to obtain solution B, and then add solution B to solution A, stir at a speed of 380 r / min for 30 minutes to obtain silica sol; Wherein, the concentration of hydrochloric acid is 35wt%; S2: dissolving 4 parts of silicotungstic acid, 0.6 parts of surfactant and 1.5 parts of trimethylsilyl imidazole in 90 parts of water by mass to obtain a silicotungstic acid solution, and then adding 18 parts of silica sol obtained in step S1 to the silicotungstic acid solution to obtain a suspension, stirring at a speed of 280 r / min for 6 hours, filtering to obtain a filter cake, washing, and then drying at 120° C. for 11 hours, and finally calcining at 500° C. for 4 hours to obtain the self-cleaning composite material; The surfactant is prepared by mixing disodium EDTA and sodium dodecylbenzene sulfonate in a mass ratio of 2:3; The preparation method of the waterproof and anticorrosive coating comprises the following steps: (1) Add 15 parts of water, 1.5 parts of self-cleaning composite material, 1 part of silica gel particles, and 0.5 parts of dispersant into a stirring tank, stir at a low speed until uniform, then add 15 parts of water-based hydroxy acrylic resin, stir at a high speed for 15 minutes, and obtain a stable slurry; (2) Mix 59 parts of water-based fluorocarbon resin and the stable slurry obtained in step (1) by weight, add 0.3 parts of defoamer, 0.7 parts of thickener and 2 parts of film-forming agent after stirring, and stir at high speed for 20 minutes to obtain component A; (3) By mass, 95 parts of component A obtained in step (2) and 6 parts of component B were mixed and stirred at high speed for 10 minutes to obtain the waterproof and anti-corrosion coating.

[0019] The comparative example adopts the method of application number CN202210915407.1 to prepare the waterproof and anticorrosive coating, which is different from the present embodiment in that no silica gel particles are added; Performance Testing 1. Anti-fouling grade test: The waterproof and anti-corrosion coatings prepared in this embodiment and the comparative example were evenly applied on an asbestos-free fiber cement flat plate according to the test requirements of method A (standard state method) in GB / T9780-2013 "Test method for anti-fouling of architectural coatings" to form a coating with a coating thickness of 160 μm, and a test coated plate was obtained; the test was conducted again after 30 days; 2. Methyl orange decolorization rate test: Prepare a 20 mg / L methyl orange aqueous solution, and then cut out a 10 cm area of ​​the prepared test plate. 2 The test cube is placed in 200 mL of the methyl orange aqueous solution, and irradiated under a UV lamp for 180 min with an average light intensity of 500 Lux, and the decolorization rate of methyl orange is measured; 3. Toughness test: According to ASTM D522-93a (2018) "Standard Test Method for Impact Resistance of Coatings", a mandrel bending test is used to bend the coated specimen to 180 degrees, and then observe whether the coating has cracks, peeling, etc. The toughness of the coating is evaluated by measuring the maximum bending radius at which the coating is not damaged during the bending process.

[0020] After testing, the stain resistance test result of this embodiment is level 0, and the result of the test again after 30 days is level 1, the decolorization rate of methyl orange is 96.7%, and the toughness test result is 7.7mm; The stain resistance test result of the comparative example was grade 0, and the result of the re-test after 30 days was grade 2. The decolorization rate test result of methyl orange was 96.2%, and the toughness test result was 7.3 mm.

[0021] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: Silica gel is a porous solid material with a large number of micropores and mesopores inside. These pore structures make silica gel have a high specific surface area, so that it can absorb and store moisture. When silica gel is in a humid environment, the surface in its pores can absorb water vapor molecules in the air. When the humidity on the coating surface decreases or the temperature rises due to solar radiation, the silica gel particles will slowly release the stored moisture, and the moisture adsorbed in the silica gel pores will gradually desorb and release into the surrounding environment, thereby promoting the photocatalytic reaction. Silica gel particles have strong hygroscopicity and can quickly absorb and release moisture. Adding silica gel particles to the coating can form tiny water absorption points on the surface of the coating, which can maintain the wetness of the coating surface, thereby promoting the photocatalytic reaction and accelerating the degradation of pollutants. Silica gel has excellent weather resistance and chemical stability, and is not easy to react with other components in the coating. Silica gel particles can resist the erosion of ultraviolet rays and other environmental factors, and extend the service life of the coating. Therefore, compared with the comparative example, the contamination resistance level of the waterproof and anti-corrosion coating in this embodiment is improved from level 2 to level 1 after 30 days, and the decolorization rate test result of methyl orange is improved from 96.2% to 96.7%; The addition of silica gel particles improves the wettability of the coating, making it easier for water droplets to spread and roll on the coating surface, reducing the residence time of water droplets on the coating surface, reducing the risk of stain adhesion, and increasing the contact area between the coating and the water droplets, so that the water droplets carry more dust and pollutants away from the coating surface, improving the self-cleaning effect of the coating; The water released by the silica gel particles continuously supplies silicotungstic acid for photocatalytic reaction, generating more active groups such as hydroxyl free radicals. These active groups have strong oxidizing ability, which enables silicotungstic acid to continuously perform photocatalytic reaction, effectively degrade organic pollutants on the coating surface, and further improve the cleanliness of the coating; silicotungstic acid, as a photocatalyst, requires the participation of water to generate active substances such as hydroxyl free radicals during the photocatalytic degradation of organic pollutants. By mixing silica gel particles and silicotungstic acid in the coating to play a synergistic role, the silica gel particles can continuously provide the required water for silicotungstic acid, ensuring the smooth progress of the photocatalytic reaction and degrading pollutants; By adding silica gel particles and using them in combination with self-cleaning composite materials, the silica gel can continuously supply water to silicotungstic acid. The water absorption and release characteristics of the silica gel particles combined with the photocatalytic properties of silicotungstic acid significantly improve the self-cleaning ability of the coating and the degradation efficiency of organic pollutants. Photocatalytic technology is used to degrade pollutants without the need for additional energy input, which is energy-saving and environmentally friendly. At the same time, it ensures that the coating has excellent waterproof, anti-corrosion and construction performance.

[0022] Example 2: The above Example 1 adds silica gel particles to combine the water absorption and release properties of silica gel particles with the photocatalytic properties of silicotungstic acid, thereby improving the self-cleaning ability of the coating and the degradation efficiency of organic pollutants. In order to further improve the self-cleaning ability of the coating and the degradation efficiency of organic pollutants, further improvements are made on the basis of Example 1.

[0023] Step (1) Before adding, the silica particles are pre-mixed and stirred with ethanol to form a uniform suspension; Wherein, the particle size of silica gel particles is 10nm-10μm; For this embodiment, an experiment was conducted on the basis of the first embodiment. The difference between this embodiment and the first embodiment is that the particle size of the silica gel particles is 10 nm-10 μm, and they are pre-mixed and stirred with ethanol before adding in step (1) to form a uniform suspension; After testing, the stain resistance test result of this embodiment was grade 0, and the result of the test again after 30 days was grade 1. The decolorization rate test result of methyl orange was 97.4%, and the toughness test result was 8.0 mm.

[0024] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: The silica gel particles are pre-mixed with ethanol, and the wettability and dispersibility of ethanol are utilized to better disperse the silica gel particles in the coating. As an organic solvent, ethanol can reduce the surface tension between the silica gel particles, reduce the agglomeration phenomenon, and make the silica gel particles more evenly distributed in the coating. After the pre-formed silica gel suspension is added to the coating, the presence of ethanol can slow down the sedimentation rate of the silica gel particles, improve the stability of the coating system, and maintain the stability of the coating performance during storage and construction. As a volatile solvent, ethanol will evaporate rapidly during the drying process of the coating, promoting the film-forming process of the coating. At the same time, the volatilization of ethanol will also drive the uniform distribution of the silica gel particles on the coating surface, further improving the performance of the coating. The silica gel particles are 10nm-10μm, which can ensure the functionality of the silica gel particles while improving their dispersibility in the coating. Silica gel particles with moderate particle size can form a uniform microporous structure in the coating. These microporous structures can improve the air permeability and wettability of the coating. At the same time, the water absorption and release characteristics of the silica gel particles can also be better utilized, thereby further improving the self-cleaning ability of the coating and the degradation efficiency of organic pollutants. Silica gel particles with moderate particle size will not significantly increase the viscosity of the coating, so it will not affect the construction performance of the coating. On the contrary, they can be evenly dispersed in the coating, making the coating easy to operate during construction and improving construction efficiency and quality.

[0025] Example 3: The above-mentioned Example 2 improves the self-cleaning ability of the coating and the degradation efficiency of organic pollutants by improving the particle size of the added silica gel particles and the method of adding the silica gel particles. In order to further improve the self-cleaning ability of the coating and the degradation efficiency of organic pollutants, further improvements are made on the basis of Example 2.

[0026] The component A also contains rubber powder. Specifically, in step (1), the rubber powder is added to the stirring tank. The rubber powder is 1-3 parts by weight and has a particle size of 1-10 μm.

[0027] For this embodiment, an experiment was conducted on the basis of the second embodiment. The difference between this embodiment and the second embodiment is that in step (1), 2 parts of rubber powder are added to the stirring tank; After testing, the stain resistance test result of this embodiment is level 0, and the result of testing again after 30 days is also level 0. The decolorization rate test result of methyl orange is 98.3%, and the toughness test result is 8.8 mm.

[0028] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: Rubber powder has a certain elasticity and absorption capacity. It can absorb part of the volume change when the paint absorbs water and expands, reducing the direct pressure on the paint structure, thereby maintaining the stability and durability of the paint; the addition of rubber powder improves the toughness of the paint, making the paint have better crack resistance and durability when subjected to external stress or internal expansion pressure, thereby extending the service life of the paint and reducing coating damage caused by stress concentration; Rubber powder can change the stress distribution state inside the coating, dispersing the concentrated compressive stress to a wider area; reducing the cracking or peeling of the coating caused by excessive local stress, thereby improving the overall performance of the coating; the addition of rubber powder further promotes the wettability and air permeability of the coating surface, and improves the self-cleaning ability of the coating. Since rubber powder forms tiny pore structures in the coating, these pore structures promote the diffusion and discharge of water and pollutants; rubber powder, silica gel particles and self-cleaning composite materials produce synergistic effects in the coating. The elasticity and absorption capacity of rubber powder can maintain the stability and dispersibility of silica gel particles and self-cleaning composite materials in the coating, thereby further improving the performance of the coating; The addition of rubber powder improves the stability and self-cleaning ability of the coating, allowing the coating to be used in more fields and occasions, improving the adaptability of the coating and broadening the scope of use of the coating.

[0029] Embodiment 4: The above embodiment 3 improves the self-cleaning ability of the coating and the degradation efficiency of organic pollutants by adding rubber powder. In order to further improve the self-cleaning ability of the coating and the degradation efficiency of organic pollutants, further improvements are made on the basis of embodiment 3.

[0030] The rubber powder is also loaded with nano-silicon dioxide, where the nano-silicon dioxide accounts for 5%-15% of the rubber powder mass; The steps of loading the rubber powder with nano-silicon dioxide are as follows: Dispersing rubber powder in ethanol to form a uniform suspension; Slowly adding the nano-silica sol prepared in step S1 to the suspension of rubber powder while stirring to ensure that the sol is evenly distributed on the surface of the rubber powder or penetrates into the rubber powder; The rubber powder loaded with nano-silica sol is dried to remove the solvent; then, the rubber powder is cured at 100-150° C. to obtain the rubber powder loaded with nano-silica; For this embodiment, an experiment is conducted on the basis of the third embodiment. The difference between this embodiment and the third embodiment is that the rubber powder is loaded with nano-silicon dioxide accounting for 10% of its mass; After testing, the stain resistance test result of this embodiment is level 0, and the result of testing again after 30 days is also level 0, the decolorization rate test result of methyl orange is 98.9%, and the toughness test result is 9.3 mm.

[0031] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: Rubber powder itself has good elasticity and toughness. After loading nano-silica, this composite material can more effectively absorb and disperse external impact or internal expansion pressure, thereby significantly improving the durability and crack resistance of the coating; Nano-silicon dioxide is easy to agglomerate due to its high specific surface area and surface activity, but loading it on rubber powder can effectively utilize the large specific surface area and pore structure of rubber powder to achieve uniform dispersion of nano-silicon dioxide particles, prevent agglomeration, and improve the overall uniformity and stability of the coating; Nano-silicon dioxide has many excellent properties such as photocatalysis, UV resistance, and hardness enhancement. After being loaded on rubber powder, these properties can be effectively retained and exerted in the coating. At the same time, the addition of rubber powder also makes the coating have better waterproofness and wear resistance. Nano-silicon dioxide, as a photocatalyst, requires the participation of water in the process of photocatalytic degradation of organic pollutants. Nano-silicon dioxide loaded on rubber powder can be more evenly distributed in the coating, and synergizes with silica gel particles to continuously provide the required water for the photocatalytic reaction, thereby significantly improving the self-cleaning ability of the coating and the degradation efficiency of organic pollutants. The addition of rubber powder and nano-silica affects the rheology and viscosity of the coating. By precisely controlling the loading ratio and particle size distribution of rubber powder and nano-silica, the rheology and viscosity of the coating can be optimized to meet different construction conditions and application requirements.

[0032] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A waterproof and anti-corrosion coating, characterized in that: The following raw materials are included by weight: 90-100 parts of component A, 5-8 parts of component B; The component A comprises the following raw materials, by mass: 55-60 parts of water-based fluorocarbon resin, 10-20 parts of water-based hydroxy acrylic resin, 1-2 parts of self-cleaning composite material, 0.5-2.5 parts of silica gel particles, 0.2-1 parts of dispersant, 0.1-0.5 parts of defoamer, 0.5-1 parts of thickener, 1-2 parts of film-forming agent, and 10-20 parts of water; The B component is a curing agent.

2. A process for preparing the waterproof and anticorrosive coating according to claim 1, characterized in that: The specific steps include: (1) adding water, self-cleaning composite material, silica gel particles, and dispersant into a stirring tank, stirring at a low speed until uniform, and then adding water-based hydroxy acrylic resin, stirring at a high speed to obtain a stable slurry; (2) mixing the aqueous fluorocarbon resin with the stable slurry obtained in step (1) and stirring, adding a defoamer, a thickener, and a film-forming agent after stirring evenly, and stirring at high speed to obtain component A; (3) Component A obtained in step (2) is mixed with component B, and stirred at high speed to obtain the waterproof and anti-corrosion coating.

3. The preparation process of the waterproof and anticorrosive coating according to claim 2, characterized in that: The method for preparing the self-cleaning composite material comprises the following steps: S1: tetraethyl orthosilicate and anhydrous ethanol are mixed and stirred to obtain solution A; then, anhydrous ethanol, water and hydrochloric acid are mixed and stirred to obtain solution B; then, solution B is added to solution A and stirred to obtain silica sol; S2: dissolving silicotungstic acid, surfactant and trimethylsilyl imidazole in water to obtain a silicotungstic acid solution, then adding the silica sol obtained in step S1 to the silicotungstic acid solution to obtain a suspension, filtering to obtain a filter cake, washing, drying and calcining to obtain the self-cleaning composite material; The surfactant is at least one of disodium EDTA and sodium dodecylbenzene sulfonate.

4. The preparation process of the waterproof and anticorrosive coating according to claim 2, characterized in that: Step (1) Before adding the silica gel particles, they are pre-mixed and stirred with ethanol to form a uniform suspension.

5. The preparation process of the waterproof and anticorrosive coating according to claim 3, characterized in that: The particle size of the silica gel particles is 10 nm-10 μm.

6. The preparation process of the waterproof and anticorrosive coating according to claim 2, characterized in that: The component A also contains rubber powder. Specifically, the rubber powder is added to the stirring tank in step (1).

7. The preparation process of the waterproof and anticorrosive coating according to claim 6, characterized in that: The rubber powder is 1-3 parts by mass.

8. The preparation process of the waterproof and anticorrosive coating according to claim 6, characterized in that: The particle size of the rubber powder is 1-10 μm.

9. The preparation process of the waterproof and anticorrosive coating according to claim 6, characterized in that: The rubber powder is also loaded with nano silicon dioxide.

10. The preparation process of the waterproof and anticorrosive coating according to claim 9, characterized in that: The nano silicon dioxide accounts for 5%-15% of the weight of the rubber powder.

Citation Information

Patent Citations

  • Nano titanium dioxide photocatalytic disinfecting and purifying coating

    CN108587342A

  • Environment-friendly putty powder with TVOC removal function

    CN108641460A

  • Humidity-adjusting interior wall coating prepared from roasted diatomite

    CN109306216A

  • Waterproof anticorrosive paint for concrete and preparation method of waterproof anticorrosive paint

    CN115197614A

  • Rubber runway coiled material bottom layer material and preparation method thereof

    CN117106250A